2012
DOI: 10.4172/2155-9880.1000218
|View full text |Cite
|
Sign up to set email alerts
|

The Appraisal-Trial: Evaluating RESTEN-MPTM in Patients with Bare Metal Stent De Novo Native Coronary Artery Lesions

Abstract: Neointimal hyperplasia is one of the key components of the restenotic process. The aim of this study was to evaluate the efficacy and safety of a microbubble delivery of c-myc antisense peptide in reducing restenosis after coronary stenting in de novo stenosis with intravascular ultrasound. A Multi-Link Zeta bare metal stent was implanted in de novo coronary artery lesions (RD ≥ 2.5-≤ 4.0 mm; TL ≥ 15-≤ 30 mm in length). Serial intravascular ultrasound analyses were performed in 25 lesions. A dose of 16mg RESTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A Phase I trial of Resten-NG carried out by AVI BioPharma enabled the determination of its bioavailability in solid tumor patients and established the feasibility of using PMOs in human cancer (Devi et al, 2005 ). Moreover, local delivery was feasible and safe in a related target disease, cardiovascular restenosis that involves neointimal hyperplasia (Kipshidze et al, 2003 , 2004 ) and a Phase II study reported positive results following local delivery (Kipshidze et al, 2007 ; Philipp et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…A Phase I trial of Resten-NG carried out by AVI BioPharma enabled the determination of its bioavailability in solid tumor patients and established the feasibility of using PMOs in human cancer (Devi et al, 2005 ). Moreover, local delivery was feasible and safe in a related target disease, cardiovascular restenosis that involves neointimal hyperplasia (Kipshidze et al, 2003 , 2004 ) and a Phase II study reported positive results following local delivery (Kipshidze et al, 2007 ; Philipp et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was successfully tested in a rabbit balloon injury model ( Kipshidze et al, 2002 ) and porcine restenosis model ( Kipshidze et al, 2003 ; Kipshidze et al, 2002 ) with promising results: significant reduction of the neointimal area with concomitant MYC inhibition. Although this was further validated in a Phase II trial with positive results ( Philipp, 2012 ), the drug was not developed beyond this point.…”
Section: Myc’s Involvement In Diseases and Conditionsmentioning
confidence: 99%